Spatial competition between health care providers: effects of standardization - Björn A. Kuchinke; Jürgen Zerth; Nadine Wiese (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2009)
In the international health care literature there is a broad discussion on impacts of competition in health care markets. But aspects of standardization in regional health care markets with no price competition received comparatively little attention. We use a typical Hotelling-framework (reference case) to analyze a regional health care market with two health care providers competing in (vertical) quality after the scope of medical treatment is set (horizontal quality). We conclude, that in the reference case both health care provider will use vertical quality to separate from each other. In the next step (standardization case) we introduce one health care provider to be the standard leader in vertical quality. In the standardization case a more homogeneous supply can be expected. But, there is a higher possibility that the standard follower has to leave the regional health care market.
Keywords: 330; Gesundheitswesen; Dienstleistungsqualität; Hotelling Modell; Normung; Räumlicher Wettbewerb; Theorie